Interferon-Driven Immune Dysregulation in Down Syndrome: A Review of the Evidence - Chung H; Green PH; Wang TC; Kong XF (Dove Medical Press, 2021)
Howard Chung,1,2 Peter HR Green,1,3 Timothy C Wang,1 Xiao-Fei Kong1,3 1Division of Digestive and Liver Diseases, Department of Medicine, Columbia University Irving Medical Center, New York, NY, 10032, USA; 2Department of Internal Medicine, Icahn School of Medicine at Mount Sinai/Queens (Queens Hospital Center), Jamaica, NY, 11432, USA; 3Celiac Disease Center, Department of Medicine, Columbia University Medical Center, New York, NY, 10032, USACorrespondence: Xiao-Fei KongDivision of Digestive and Liver Diseases, Department of Medicine, Columbia University Irving Medical Center, 622 West 168th ST, PH7W Suite 318, New York, NY, 10032, USAEmail xk2137@cumc.columbia.eduAbstract: Down syndrome (DS) is a unique genetic disease caused by the presence of an extra copy of chromosome 21, which carries four of the six interferon receptor (IFN-R) genes on its long arm. Recent studies reporting higher levels of interferon-stimulated gene (ISG) expression in primary immune cells studied ex vivo have suggested that the additional copies of the IFN-R genes in DS result in mild interferonopathy. In this review, we analyze the potential clinical and immunological impacts of this interferonopathy in DS. We performed a literature review to explore the epidemiology and risks of celiac disease, type 1 diabetes, thyroid dysfunction, mucocutaneous manifestations, infectious diseases (including COVID-19), and Alzheimer's disease in individuals with DS relative to the general population with or without iatrogenic exposure to interferons. We analyzed immunophenotyping data and the current experimental evidence concerning IFN-R expression, constitutive JAK-STAT activation, and ISG overexpression in DS. Despite the lack of direct evidence that implicating this mild interferonopathy directly in illnesses in individuals with DS, we highlight the challenges ahead and directions that could be taken to determine more clearly the biological impact of interferonopathy on various immune-related conditions in DS.Keywords: down syndrome, interferon receptors, JAK-STAT, celiac disease, T cells, gene dosage effect